PENGARUH PELAKSANAAN SANKSI TATA TERTIB TERHADAP DISIPLIN SISWA DI SMA NEGERI 1 TAPUNG HILIR KABUPATEN KAMPAR - Revina Revina; Zahirman Zahirman; Supentri Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is motivated by problems that arise from interviews conducted by researchers ie students in SMA Negeri 1 have a bad attitude of discipline. The school has made various rules or rules along with severe sanctions with point system and additional punishment, this is done to foster discipline in student. The purpose of this study to determine the effect of implementation of disciplinary sanctions on the discipline and effectiveness of the implementation of sanctions against student discipline in SMA Negeri 1 Tapung Hiir Kampar Regency. This research method using quantitative descriptive analysis, the data in the analysis by using simple linear regression. Based on the results of research can be concluded that the percentage of respondents' responses recapitulation answer about the effect of implementation of sanctions against student discipline in SMA Negeri 1 Tapung Hilir Kampar Regancy, The effect of sanctions on student discipline in SMA Negeri 1 Tapung Hilir Kabupaten Kampar is 63%. Implementation Effective sanctions in the formation of discipline. This can be seen from 64.4% of respondents who stated that the implementation of sanctions in SMA Negeri 1 Tapung Hilir Kampar Regency included in the category is quite good or quite effective.Keyword : Implementation of sanction, discipline of student